Mnemonic Techniques and Lie Detection: Accuracy of Truth and Deception Judgments in Repeated Accounts - Aleksandras Izotovas; Aldert Vrij; Leif A. Strömwall (Psichologija, 2021)
This study was an examination into whether the use of memory-enhancing techniques (mnemonics) in interviews can be helpful to distinguish truth tellers from liars. In the previous study (Izotovas et al., 2018), it was found that when mnemonic techniques were used in the interview immediately after the event, truth-tellers reported more details than liars in those immediate interviews and again after a delay. Moreover, truth-tellers, but not liars, showed patterns of reporting indicative of genuine memory decay.